Changes of breast and axillary surgery patterns in patients with primary breast cancer during the past decade - Riedel, Fabian; Heil, Jörg; Golatta, Michael; Schäfgen, Benedikt; Fastner, Sarah; Schott, Sarah; Rom, Joachim; Schütz, Florian; Sohn, Christof; Hennigs, André (Archives of gynecology and obstetrics, 2019)
PurposeBreast-conserving therapy (BCT) is the standard procedure for most patients with primary breast cancer (BC). By contrast, axillary management is still under transition to find the right balance between avoiding of morbidity, maintaining oncological safety, and performing a staging procedure. The rising rate of primary systemic therapy creates further challenges for surgical management.MethodsPatients with primary, non-metastatic BC treated between 01.01.2003 and 31.12.2016 under guideline-adherent conditions were included in this study. For this prospectively followed cohort, breast and axillary surgery patterns are presented in a time-trend analysis as annual rate data (%) for several subgroups.ResultsOverall, 6700 patients were included in the analysis. While BCT rates remained high (mean 2003-2016: 70.4%), the proportion of axillary lymph node dissection has declined considerably from 80.1% in 2003 to 16.0% in 2016, while the proportion for sentinel lymph node biopsy (SLND) has increased correspondingly from 10.3 to 76.4%. Among patients with cT1-2, cN0 breast cancer receiving BCT with positive SLND, the rate of axillary completion has decreased from 100% in 2008 to 24.4% in 2016.ConclusionsIn the past decade, SLNB has been established as the standard procedure for axillary staging of clinically node-negative patients. Surgical morbidity has been further reduced by the rapid implementation of new evidence from the ACOSOG Z0011 trial into clinical routine. The results reflect the transition towards more individually tailored, less invasive treatment for selected patient subgroups, especially in regards to axillary lymph node management.